2011
DOI: 10.1523/jneurosci.5319-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Calcium Waves Traveling through Astrocytic NetworksIn Vivo

Abstract: Macroscopic changes in cerebral blood flow, such as those captured by functional imaging of the brain, require highly organized, large-scale dynamics of astrocytes, glial cells that interact with both neuronal and cerebrovascular networks. However, astrocyte activity has been studied mainly at the level of individual cells, and information regarding their collective behavior is lacking. In this work, we monitored calcium activity simultaneously from hundreds of mouse hippocampal astrocytes in vivo and found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
202
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(223 citation statements)
references
References 54 publications
20
202
1
Order By: Relevance
“…5c). However, as TTX treatment alone has been demonstrated to be sufficient to block flavoprotein-dependent autofluorescence in rat somatosensory cortex 29 as well as blocking synchronous, infraslow largescale astrocytic calcium waves 62 , we also examined the dependency of our observed infraslow activity on specifically excitatory glutamatergic transmission and found that DNQX and AP5 treatment also abolished infraslow functional organization (Fig. 5).…”
Section: Discussionmentioning
confidence: 97%
“…5c). However, as TTX treatment alone has been demonstrated to be sufficient to block flavoprotein-dependent autofluorescence in rat somatosensory cortex 29 as well as blocking synchronous, infraslow largescale astrocytic calcium waves 62 , we also examined the dependency of our observed infraslow activity on specifically excitatory glutamatergic transmission and found that DNQX and AP5 treatment also abolished infraslow functional organization (Fig. 5).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, ICWs can also occur spontaneously without specific triggers. Spontaneous ICWs have been observed in retinal pigment epithelial cells (270), the intact retina in vitro and in vivo (193), brain slices of the developing neocortex (394), Bergmann glia (astrocytes in the molecular layer) of the in vivo cerebellum (161), and hippocampal astrocytes in vivo (192). The frequency of these spontaneous ICWs can be increased by lowering extracellular Ca 2ϩ (343,394,413), an effect that may result from increased connexin hemichannel opening and ATP release (11) (see sect.…”
Section: Ca 2؉ Wave Initiationmentioning
confidence: 99%
“…Equally important is the fact that in tissue culture, many of the organ characteristics, such as the extracellular matrix, variety of cell types, extent of cell coupling, and cell differentiation, are lost or significantly altered. At present, there are fewer reports of ICWs in vivo in organs like the brain, liver, and lung (161,192,265,292) and therefore, as yet, insufficient supportive data for specific physiological responses of ICWs. However, this situation is rapidly changing.…”
Section: Functions Of Intercellular Ca 2؉ Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, large regenerative waves spanning all the observable cells are sometimes (though rarely) observed (cf. [14]). Our results indicate that this could be linked to a transient decrease of gapjunction coupling levels, effectively leading to a reduction of the network mean degree, or to a restriction of gap-junction coupling to a few neighbors.…”
Section: Topological Influencesmentioning
confidence: 99%